Impact of frontline demonstration on rapeseed productivity in South-western part of Punjab: IMPACT OF FRONTLINE DEMONSTRATION ON RAPESEED PRODUCTIVITY IN SOUTH-WESTERN PUNJAB - BALKARAN SINGH SANDHU; NIRMALJIT SINGH DHALIWAL (Journal of Oilseeds Research, 2019)
Farmers grow non-canola local varieties viz., Reli and Rajasthani of rapeseed with lower seed rate, delayed sowing, low plant population, improper nutrient management and inadequate plant protection in Muktsar Sahib District, Punjab state. Also, the local varieties contain high erucic acid and high glucosinolates, considered to be undesirable to consumers from the health perspective. The Krishi Vigyan Kendra, Sri Muktsar Sahib, Punjab conducted frontline demonstrations (FLDs) during rabi 2015-16 to 2017-18 with improved technologies including better variety (GSC 7), optimum seed rate and spacing, line sowing, soil test based nutrient management and need based plant protection to show the productivity potential and profitability under farmers'situations. The mean seed yield improved by 11.7 per cent with higher gross monetary returns, net returns and BC ratio with improved technology compared to farmers' practice during the three year period. The technology gap decreased from675 kg/ha to 145 kg/ha indicating the sustainability of the improved technology. The extension gap increased from 70 kg/hato 330 kg/ha, due to higher yields with the improved technology. The technology index decreased from 30.3 to 6.5 per cent indicating the feasibility of the improved technology in farmers' fields. In order to improve the productivity of rapeseed-mustard in Muktsar Sahib district, concerted efforts have to be made involving all the stakeholders to popularize the improved technologies.